Quality in higher education: the maintenance phase of the internal quality assurance system in one Portuguese University - Jesus-Silva, Natacha (2020)
Theoretically, it is easy to enumerate the advantages of the existence of an IQAS (Internal Quality Assurance System) implemented in an accredited (Higher Education Institution) HEI. In practice, it is very difficult after obtaining certification / accreditation, maintaining it in order to feel the effects of quality management as a whole. [...]